Horizontal Product Diversification Strategy to Increase the Competitiveness of MSMEs - Hariyanti, Sri; Sudarmiatin; Wardana, Ludi Wishnu (Asian Journal of Management Analytics, 2023)
The development of the culinary business in Indonesia is increasingly rapid and diverse in meeting the increasingly complex needs of society in line with changes in life style. Companies/MSMEs are required to be able to fulfill consumer requests or desires, so that they can compete, efforts need to be made to increase product quality and variety (horizontal diversification of products) in order to produce products that consumers are interested in. This research aims to find out how the horizontal product diversification strategy is implemented at CV.Bolu Ketan Minister of Forestry and to determine the increase in CV's competitiveness. Minister of Forestry's Sticky Rice Bolu after implementing a horizontal product diversification strategy. Therefore, a qualitative approach is used to determine the condition of natural objects, where the researcher is the key instrument. The results of this research show that CV. Bolu Ketan Mendhut has implemented a horizontal product diversification strategy so that it has many flavor variants in its products and various sizes to meet consumer demand and from implementing this strategy it has apparently increased its competitiveness among its competitors.